Mathematical economics - Baldani, Jeffrey (Thomson/South-Western, 2005)
Skip the formal proofs and go straight to understanding the important concepts! MATHEMATICAL ECONOMICS gives you all the information you need to work with economic concepts at the intermediate or advanced level. How? MATHEMATICAL ECONOMICS emphasizes the use of mathematics in actual economic models, not through difficult proofs. The balance of theory and application makes this the economics textbook that will help you ace the class and get ready for the real world at the same time